Traditional knowledge on integrated pest and weed management in chayote (Sechium edule (Jacq.) Sw.) crops from localities of Chiapas, Mexico (2017)
This research was carried out in Villaflores and Villa Corzo, located in Chiapas State of Mexico. Specifically, throughout an ethno-agronomical approach, semi-structured interviews were designed and applied to the chayote producers who were selected by random routes. The results indicate the 57.89% of chayote producers in both municipalities, have allowed to control weeds in their crops, and being a higher proportion represented by Villaflores. Given these concerns, they prefer to control weeds throughout traditional methods, basically using mattocks with frequencies of 15 to 30 days after sowing or two to four times per cycle of crop production. Both pest and diseases are mainly controlled throughout chemical methods application. A preference to perform control among periods of higher rainfall or drought is not distinguished. A considerable percentage, which reaches 44% of the interviewed population among both municipalities, report they do not need to control pests and crop diseases.